Heavy Metal Content in Soil and Medicinal Plants in High Traffic Urban Area - Princewill-Ogbonna, Ijeoma L.; Ogbonna, Princewill C. (Pakistan Journal of Nutrition, 2011)
The heavy metals (Zn, Pb and Zn) concentrations in soil and medicinal plant samples from Aba city, Nigeria using atomic absorption spectrophotometer UNICAM 919 model was evaluated in a randomized complete block design. The results showed that there was a clear accumulation of metals in soil and medicinal plants in relation to vehicular emission in the city. A highest concentration of Zn (133.56±7.70 mg/kg) in soil was obtained from X2, Pb (29.71±1.56 mg/kg) and Cd (21.11±1.28 mg/kg) was in X5. The levels of Zn, Pb and Cd in soil were 15.85±18.03 - 133.56±7.70 mg/kg, 10.06±0.36 - 29.71±1.56 mg/kg and 1.07±0.08 - 21.11±1.28 mg/kg, respectively. In medicinal plants, the highest concentration of Zn was obtained in Azadiractha indica (34.58±2.07 mg/kg), Pb was in Psidium guajava (10.47±0.93 mg/kg) and levels of Zn, Pb and Cd were 9.02±1.40 - 34.58±2.07 mg/kg, 1.55±0.35 - 10.47±0.93 mg/kg and 0.02±0.0 - 1.44±0.11 mg/kg, respectively. The concentrations of metals in soil and medicinal plant were in decreasing order: Zn>Pb>Cd. Zinc in soil significantly correlated positively with Zn (0.956, p